Estudo da sedimentação de partículas em fluidos de perfuração aquosos e olefínicos utilizando a atenuação de raios gama - Faim, João Guilherme Prates (2020)
The relevance of oil in world energy matrix motivates the search for strategies to optimize its production. In drilling stages of oil wells, drilling fluids present as one of its main functions to clean the bottom of well by carrying the drill cuttings to surface. In addition, drilling fluids, when at rest, must be able to maintain these solids in suspension. Therefore, it’s important to know the rheological properties of drilling fluids, as well as behavior of settling process in it. Thus, this dissertation aimed to study the sedimentation process of particles in different drilling fluids. For this purpose, the effect of addition of xanthan gum (GX) and the effect of hematite concentration on rheology and sedimentation of suspensions in drilling fluids was evaluated. The sedimentation was studied by using the Gamma-ray Attenuation Technique, a nondestructive approach that allows the monitoring of volumetric concentration of solids as a function of position and time. The addition of xanthan gum directly affected the rheology of the fluid, providing pseudoplastic and thixotropic properties, and the sedimentation process, observed by particle agglomeration phenomenon and the longer duration of settling process. Regarding the effect of hematite concentration, it was noticed that fluids with larger amounts of thickening material presented greater stability during the sedimentation process, maintaining the solids in suspension for longer. In addition, constitutive equations for pressure on solids were fitted for each system. Finally it was possible to better comprehend the effect of viscosifying agente (xanthan gum) and thickening agentes (hematite) on drilling fluids’ properties.